Identification of Amino Acids Essential for Viral Replication in the HCMV Helicase-Primase Complex - Ligat, Gaetan; Da Re, Sandra; Alain, Sophie; Hantz, Sébastien (Frontiers in Microbiology, 2018)
Promising new inhibitors that target the viral helicase-primase complex have been reported to block replication of herpes simplex and varicella-zoster viruses, but they have no activity against human cytomegalovirus (HCMV), another herpesvirus. The HCMV helicase-primase complex (pUL105-pUL102-pUL70) is essential for viral DNA replication and could thus be a relevant antiviral target. The roles of the individual subunits composing this complex remain to be defined. By using sequence alignment of herpesviruses homologues, we identified conserved amino acids in the putative pUL105 ATP binding site and in the putative pUL70 zinc finger pattern. Mutational analysis of several of these amino acids both in pUL105 and pUL70, proved that they are crucial for viral replication. We also constructed, by homology modeling, a theoretical structure of the pUL105 N-terminal domain which indicates that the mutated conserved amino acids in this domain could be involved in ATP hydrolysis.